Cost-Effectiveness Analysis of the Diagnosis and Treatment of Primary Aldosteronism in Japan - Sato, M.; Morimoto, R.; Seiji, K.; Iwakura, Y.; Ono, Y.; Kudo, M.; Satoh, F.; Ito, S.; Ishibashi, T.; Takase, K. (Hormone and Metabolic Research, 2015)
Approximately 10% of cases of hypertension in Japan are caused by primary aldosteronism (PA), amounting to about 4 million patients in total. Primary aldosteronism due to unilateral aldosterone hypersecretion is potentially curable by adrenalectomy. The clinical benefits of identifying and treating PA have been reported internationally, but its cost-effectiveness is unclear. We examined whether diagnosing and treating hidden PA in hypertensive population was cost-effective compared with suboptimal treatment. Our hypothetical patient was a 50-year-old man diagnosed with stage I–III hypertension. We established a Markov decision model based on plausible clinical pathways and prognoses of PA. We applied cost-effectiveness analysis comparing a comprehensive diagnostic strategy for PA (measurement of plasma aldosterone/renin ratio, 2 loading tests, imaging, and selective adrenal venous sampling) with a suboptimal strategy to manage hypertension by medication unless the typical signs of PA or other complication were manifest. Outcome measures were expected costs, expected effectiveness, and incremental cost-effectiveness ratio. The robustness of the findings was established by one-way and scenario sensitivity analyses. The comprehensive PA diagnostic strategy increased the expected costs by 64 004 JPY and expected life-years by 0.013 compared with standard treatment. The incremental cost-effectiveness ratio for the diagnosis of PA was 4 923 385 JPY per year. Our findings were sensitive to the outcomes of screening and treatment, and the costs of continuous or periodic medication for hypertension and the treatment of stroke and its complications.
Keywords: primary hyperaldosteronism; health technology assessment; cost effectiveness; diagnostic techniques and procedures